International legal aspects of illegal food trade - Srogosz, Tomasz (Przegląd Prawa Rolnego, 2025)
This article aims to identify the mechanisms for preventing illegal food trade that are available under the international public law system, and it assesses their effectiveness. In this context, it was important to define the concept of illegal food trade, including food adulteration. In the author’s opinion, there are no international law regulations that explicitly address the prevention of illegal food trade, nor is there a legal definition of this phenomenon other than the concept of food adulteration proposed in the draft guidelines of the Codex Alimentarius Commission. The author further argues that the mechanisms existing within the WTO are inadequate for combatting illegal trade, whereas the effective instruments seem to be those institutions, regulations and procedures that are specific to international criminal law.